2021
DOI: 10.3390/agriculture11090834
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Plant Morphology Facilitating Progressive Yield Increases of japonica Inbred Rice since the 1980s in East China

Abstract: Grain yield was greatly increased during the genetic improvement of japonica inbred rice since the 1980s in Jiangsu, east China; thus, an improved plant morphology should be expected, considering that plant morphology is a decisive factor determining grain yield. Twelve representative japonica inbred rice released from 1983 to 2013 were grown in the same fields in 2019 and 2020. Grain yield increased (p < 0.01) at 63.3 kg ha−1 year−1 across 2 years among rice cultivars released in different periods. The gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Grain yield is determined by the plant biomass and harvest index. In the past century, substantial increases in rice yield have come from the progress of the chemical fertilizer industry, the "Green Revolution", and the application of hybrid rice [22]. For plant height, rice breeding projects have experienced three stages, such as dwarf (70 cm), semi-dwarf (90 cm), and semi-tall (110 cm).…”
Section: Plant Height Is Closely Correlated With Yield In Ricementioning
confidence: 99%
“…Grain yield is determined by the plant biomass and harvest index. In the past century, substantial increases in rice yield have come from the progress of the chemical fertilizer industry, the "Green Revolution", and the application of hybrid rice [22]. For plant height, rice breeding projects have experienced three stages, such as dwarf (70 cm), semi-dwarf (90 cm), and semi-tall (110 cm).…”
Section: Plant Height Is Closely Correlated With Yield In Ricementioning
confidence: 99%
“…The contribution of grain yield components to genetic yield gain was well documented, although the results were not entirely consistent. The yield increased during the genetic improvement as a result of a larger sink size through panicle per m 2 [6], spikelets per panicle [7,10], and a coordinated increase in panicles per m 2 , spikelets per panicle, and filled-grain percentage [11]. Peng et al [8] concluded that the positive yield increase was not attributable to any single yield component.…”
Section: Correlation Analysismentioning
confidence: 99%
“…Most existing literature suggests a pronounced yield increase over years; for example, Anzoua et al [6] estimated a 2.55 g m −2 year −1 yield gain of rice varieties released from 1905 to 1988 in Northern Japan. Improvements for high yield were associated with an enlarged sink size potential [6,7], an increased biomass accumulation and/or harvest index [8], an optimized plant morphology [4,9], and a coordinated source-sink balance [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of high-yielding rice and ordinary rice are very distinct. For example, the former has a higher unit yield, larger panicles, more grains, denser growth, greener stems, lusher leaves, higher water content, and stronger disease resistance than the latter [18][19][20][21][22]. These characteristics of high-yielding rice significantly impact key processes of traditional rice combine harvesting, including threshing separation, cleaning, and grain transportation.…”
Section: Introductionmentioning
confidence: 99%